2019
DOI: 10.1177/1359105319888278
|View full text |Cite
|
Sign up to set email alerts
|

Peer relationship profiles in rural Chinese adolescents: Longitudinal relations with subjective well-being

Abstract: Using two waves of data, this study aimed to identify the peer relationship profiles of 1295 rural Chinese adolescents based on a person-centered approach and to examine the interactions among these profiles, left-behind status, and gender in predicting subsequent subjective well-being. Latent profile analyses identified four profiles: a socially competent profile, a socially accepted profile, an isolated profile, and a rejected profile. These profiles were linked to left-behind status (i.e. both-parent migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
1
6
1
Order By: Relevance
“…In terms of RQ1, we compared the SWB of left-behind youth with non-left-behind peers. Contrary to our first hypothesis and the literature concerning SWB of left-behind adolescents in rural China [ 44 , 45 ], the results showed that these two groups of adolescents did not differ in SWB. This finding may indicate that “hopes and hurdles” may coexist in adolescent adaption following parental migration in urban China [ 74 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In terms of RQ1, we compared the SWB of left-behind youth with non-left-behind peers. Contrary to our first hypothesis and the literature concerning SWB of left-behind adolescents in rural China [ 44 , 45 ], the results showed that these two groups of adolescents did not differ in SWB. This finding may indicate that “hopes and hurdles” may coexist in adolescent adaption following parental migration in urban China [ 74 ].…”
Section: Discussioncontrasting
confidence: 99%
“…RQ1: do left-behind and non-left-behind youth differ in SWB? As parental migration and subsequent changes in adolescent living arrangements generate significant stress into their life [ 44 , 45 ], we anticipated that left-behind youth might report a lower level of SWB than their non-left-behind peers.…”
Section: Introductionmentioning
confidence: 99%
“…Peer relationships are interpersonal relationships established and developed through the process of communication between individuals at similar levels of psychological development (3). Perceiving good peer relationships can help adolescents gain a sense of belonging within their peer group (4), and are critical to the positive development of their cognitive and social skills, as well as academic adaptation (5). In contrast, perceiving negative peer relationships make it difficult for adolescents to control their emotions (6), which may even lead to psychological problems such as anxiety, depression, and other mental disorders (7).…”
Section: Introductionmentioning
confidence: 99%
“…Findings were consistent in considering the positive peer relationship as a protective factor against internalizing and externalizing behaviors [ 138 142 ], depression [ 143 145 ], anxiety [ 146 ], self-harm [ 147 ] and suicide [ 148 ], and as a favorable factor for positive affect [ 149 , 150 ], increased happiness [ 151 ], self-efficacy [ 152 ], optimism [ 153 , 154 ] and mental well-being [ 155 ]. In contrast, peer-hassles, friendlessness, negative peer-beliefs, peer-conflicts/isolation and peer-rejection, have been identified in the development of psychological distress among students [ 141 , 143 , 149 , 156 165 ].…”
Section: Resultsmentioning
confidence: 98%